Sex differences in frequencies of dermatoglyphic patterns by individual fingers - Miroslav Králík; Lenka Polcerová; Martin Čuta (Annals of Human Biology, 2019)
Background: The size of sex differences in dermatoglyphic features and their inter-population differences remains a subject of debate. Combining fingers in traditional dermatoglyphic methodology and omitting finger-specific variations might be a cause for uncertainty. Aim: To compare sex differences in whorl frequencies between fingers. Subjects and methods: Using meta-analytical methods, the authors studied sex differences in frequencies of whorls (log Odd Ratios) for each finger separately, including their heterogeneities (between-samples variance). The dataset of 204 population samples was extracted from published dermatoglyphic studies. Results: Aggregated effects of sex differences were significant in all fingers, except for the left 1st finger. Sex differences were higher in the right hand and increased from radial to ulnar fingers. Apart from the right 1st and 3rd fingers, heterogeneities were small and literally zero in the right 4th finger. Conclusion: Higher sex differences in ulnar fingers and the lack of interpopulation differences all over the world in the 4th finger might be caused by a stronger influence of genetic and/or hormonal factors on dermatoglyphic development of the ulnar side of the hand. It is suggested that future studies, when applying dermatoglyphic traits as markers of prenatal environment, use traits by individual fingers or their relationships within the hand.